The Genesis of the Askartor Be-Mo Deposit in the North Xinjiang, Northwest China: Evidence From Geology, Geochemistry, U-Pb, and Re-Os Geochronology - Yong, Tang; Hui, Zhang; Zheng-Hang, Lv (Frontiers in Earth Science, 2021)
The Askartor Be-Mo deposit is located in the southeastern of the Chinese Altay orogenic belt in Xinjiang, NW China. Zircon U-Pb data show that there are two periods of magmatic activities in the Askartor Be-Mo ore district, namely, the Devonian granodiorite (386.8±2.6 Ma) and biotite granite (385.4±4.4 Ma), and the Triassic two-mica granite (247.5±2.2 Ma) and muscovite granite (231.4±2.0 Ma). The zircon U-Pb age of pegmatoid orebody is 220.6±1.6 Ma which coincides with the molybdenite Re-Os isochron age of 228.7±7.1 Ma. The two-mica and muscovite granites belong to the high-K Calc-alkaline series with peraluminous features, and are characterized by high SiO2 (71.92-75.41 wt.%), and Al2O3 (13.43-15.98 wt.%), and low TiO2 (0.01-0.25 wt. %), Fe2O3 (0.11-1.14 wt.%) and CaO (0.07-0.76 wt.%). The highly fractionated element ratios of Y/Ho, Zr/Hf and Nb/Ta, and the REE tetrad effect occur in the muscovite granite, indicating the fluid exsolution occurs at the late stage of magma evolution, and the muscovite granite experienced the strong self-metasomatism. Rayleigh fractional calculations shows that the Askartor Be-Mo deposit is the product of multistage fractional crystallization of initial Be-enriched magma.